CONFIDENCE, SECURITY, AND USERS' PERCEPTION OF TECHNOLOGICAL INNOVATIONS IN FINANCIAL INSTITUTIONS: AN EXPLORATORY STUDY (CIPEEX, 2025)
In the adoption of new technologies such as artificial intelligence, blockchain and biometrics by the financial sector, trust, security and user perception play crucial roles. This study draws on a quantitative approach and previous articles to investigate how users perceive the benefits and risks of these innovations. The analysis assesses the impact of these perceptions on users' trust and willingness to adopt new financial services and products. To achieve this objective, a comprehensive literature review was used, analyzing articles published in the Scielo and Scopus databases. Articles published in English between 2018 and 2024 that assessed trust and security in the use of new financial technologies were included. Duplicate articles, opinion pieces, commentaries and case reports were excluded, resulting in a final analysis comprising 6 full articles, providing a comprehensive overview of the subject. The results reveal users' main concerns regarding the security of their data and financial transactions in the digital environment, as well as their expectations regarding the protection and privacy offered by financial institutions. The survey underlines the importance of the effectiveness of the security measures implemented by financial institutions in building user trust. The findings offer valuable insights for the development of strategies that promote trust and security in the use of these new technologies, in line with users' expectations regarding data protection and privacy. This study contributes significantly to the understanding of the relationship between trust, security and the adoption of technological innovations in the financial sector, laying a solid foundation for future research and practice in digital finance.
Keywords: security; financial institutions; technological innovations; user perception